Analisis Penentuan Lokasi Hub Transit Antara Menggunakan Metode Center of Gravity Pada Rute Sekunder 1 Kediri PT Pos Indonesia (Persero) Kantor Regional V Surabaya - Rini Ardi Ningrumsari; Dani Leonidas Sumarna; Ekra Sanggala (Bata Ilyas Educational Management Review, 2026)
PT Pos Indonesia (Persero) Regional Office V Surabaya faces a high delay rate on Secondary Route 1 Kediri. Based on SIMONA data for January–April 2026, of 1,451 checkpoint records, 832 records (57.3%) were delayed, with the dominant factors being delayed departure from the origin office (68.0%) and loading/unloading processes at transit stops (20.1%). This study aims to identify the causes of delay, determine the optimal intermediate transit hub location using the Center of Gravity (CoG) method, and formulate operational and cost improvement recommendations. The research employs a descriptive quantitative approach combining Pareto Analysis, Fishbone Diagram, and Center of Gravity across six stops (Surabaya, Mojokerto, Pare, Kediri, Tulungagung, Trenggalek) grouped into three clusters. The CoG calculation shows the optimal hub location is around Kediri City (x* = 112.2912; y* = -7.6312), reducing the Total Weighted Distance by 75.0% compared to the existing scenario. Implementing the hub in Kediri is estimated to save transportation costs by IDR 14,137,536 per month (19.3%). Improvement recommendations include establishing the hub in Kediri, improving departure SOPs, standardizing loading/unloading procedures, and upgrading the SIMONA monitoring system with real-time data.